Malignant Lymphomas of the Genitourinary Tract: a Single Center Study in Western India - Soni, Vinamrata; Gandhi, Jahnavi; Kakoty, Sneha; Shah, Ashini Hemal; Trivedi, Priti (Annals of Pathology and Laboratory Medicine, 2025)
Background: Genitourinary (GU) lymphomas are rare, accounting for <5% of extranodal lymphomas (ENL). We analyzed 43 cases of GU lymphomas in both sexes. To determine the epidemiology, clinicopathological, and immunohistochemical features of GU lymphomas. Materials and Methods: We conducted a retrospective analysis of archival cases from the Department of Oncopathology over a 7-year period (January 2018 to December 2024). Slides and blocks were retrieved and reviewed. Results: A total of 43 cases of GU lymphomas were obtained. 32 out of 43 cases (74.4%) were primary, and the rest 11 cases (25.6%) were secondary. The mean age at diagnosis was 47 years. The male: female ratio was 1.2:1. Testis (34.9%) followed by ovaries (32.6%) were the most frequently involved sites. Other less commonly involved sites were kidney, urinary bladder, penis, prostate, and vagina. Diffuse large B-cell lymphoma (DLBCL, 65.1%) was found to be the most common subtype. Neither T-cell lymphoma nor Hodgkin lymphoma cases were identified. HIV seropositivity was noted in 2 ovarian Burkitt lymphoma cases. Bone marrow involvement occurred in 4 cases. Mean follow-up duration was 11.9 months, with two patient deaths. Conclusion: GU lymphomas, though extremely rare, have a variety of subtypes. Hence, one should be cognizant of the possibility of lymphoma arising in these sites to avoid misdiagnosis. Use of immunohistochemistry and other molecular techniques further assists in its accurate diagnosis.